Deskripsi Perangkat Penilaian dalam Rancangan Pembelajaran Tematik Kelas IV Sekolah Dasar Negeri 10 Serindang Kabupaten Sambas - Syuriadi Syuriadi; Hery Kresnadi; Siti Halidjah; Kartono Kartono; Asmayani Salimi (FONDATIA, 2023)
This study generally aims to describe the assessment tools in thematic learning designs for class IV SD Negeri 10 Serindang, Sambas Regency. This study used a qualitative approach with a descriptive research method. Participants in this study served as data sources consisting of class IV A teachers as informants. Data collection techniques are documentation, interviews, and observation. The results of the study show that the attitude assessment plan is guided by Permendikbud Number 23 of 2016 with the following steps: 1) determining the attitude to be observed refers to KI 1 and KI 2 which have been determined by the school; 2) determine the indicators to be observed; 3) develop an attitude assessment format with observation techniques in the form of observation sheets and journals. Planning for knowledge assessment is guided by Permendikbud Number 23 of 2016 with steps namely planning forms and assessment techniques. The form of assessment consists of assessment of written tests, oral tests and assignments. The aspect of knowledge assessment is carried out by means of a daily assessment designed by making elements of the assessment components into the learning implementation plan. Aspects of skills assessment is carried out each per basic competency. Guided by Permendikbud Number 23 of 2016, namely by designing assessment forms and techniques such as practical techniques, products, written tests equipped with assessment component elements.